2023
DOI: 10.2147/nss.s416084
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trends in Sleep Conditions in Chinese Elderly Individuals: A National Population-Based Study

Abstract: Purpose As one of the most rapidly aging countries in the world, the elderly population is expected to reach over 400 million in China by 2032. Many studies have suggested a positive association between sleep duration and adverse health events among elderly individuals. This study aimed to investigate the sleep conditions of Chinese elderly individuals between 2005 and 2018. Patients and methods Data for 53,013 elderly individuals were taken from five cycles of the Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
1
0
0
Order By: Relevance
“…Firstly, this study used the 2008–2014 data on sleep duration. Although sleep duration and altered sleep duration in this study is similar with other recent studies ( 45 , 46 ), older adults might have a downward trend in sleep duration over the past 13 years ( 47 ), and an increased prevalence of short sleep duration ( 48 ). The change in sleep duration indicates that more attention should be paid to the impact of abnormal sleep duration on health of older adults.…”
Section: Strengths and Limitationssupporting
confidence: 89%
“…Firstly, this study used the 2008–2014 data on sleep duration. Although sleep duration and altered sleep duration in this study is similar with other recent studies ( 45 , 46 ), older adults might have a downward trend in sleep duration over the past 13 years ( 47 ), and an increased prevalence of short sleep duration ( 48 ). The change in sleep duration indicates that more attention should be paid to the impact of abnormal sleep duration on health of older adults.…”
Section: Strengths and Limitationssupporting
confidence: 89%
“… 28 In 2022, it was demonstrated that approximately 41.3% of older individuals in China slept less than 6 hours per day, with an overall average of 6.5 hours. 29 Research conducted specifically in rural areas of China identified that 52.4% of older people slept less than seven hours. 30 …”
Section: Discussionmentioning
confidence: 99%